Attitude of Iranian medical specialty trainees toward providing health care services to patients with mental disorders - Movahedi, Sana; Shariat, Seyed Vahid; Shalbafan, Mohammadreza (Frontiers in Psychiatry, 2022)
Introduction Stigma of mental illness has a negative impact on the diagnosis and treatment of these disorders. Considering the high prevalence of mental illness, the attitude of medical specialists toward mental disorders, who are front-liners in diagnosis and treatment of these patients is incredibly important. Therefore, we examined the attitude of Iranian medical specialty trainees towards providing health care services to patients with mental illness. Methods We included 143residents in the fields that have the most interactions with patients with mental disorder, including internal medicine, surgery, neurology, cardiovascular disorders and psychiatry.A demographic checklist as well as the Opening Minds Scale for Health Care Providers(OMS-HC) stigma assessment questionnaire were provided that measures five dimensions of improvement, social responsibility, social distance, exposure and other(such as risk) in health care providers toward providing the healthcare services to patient with mental disorders. Results The mean score of stigma for mental illness in medical specialty trainees was 61.36±4.83 out of 100. With psychiatric residents having the least stigmatizing attitude(58.38±3.54) and internal medicine and cardiology residents having the highest score respectively(62.96±6.05, 62.45±3.80). Within the social responsibly subscale of stigma, psychiatric trainees had the least score, and cardiology had the most. Conclusion Personal contact such as the ones with personal experience, the ones with a family member suffering from mental disorder or psychiatrist trainees who work with patients with mental disorder on a daily basis, could be a protective factor towards having a better attitude towards mental illness but maybe and simply contact is just not enough.